Tanzu za lugha : kitabu cha wanafunzi wa kidato cha tatu - Njogu, Kimani; Olodo, Robert; Kiswahili Tertiary Publishing Project (Kenya) (Nairobi : Jomo Kenyatta Foundation, 2004)
The concept and methods of teaching Swahili literature.
In Swahili.
Keywords: Swahili language -- Study and teaching; Swahili language; Form three -- Study and teaching; Swahili language; Form 3 -- Study and teaching; Swahili language; Kidato cha tatu -- Study and teaching